Multimorbidity and use of health services in the oldest old in Brazil - Priscila Maria Stolses Bergamo Francisco; Daniela de Assumpção; Aldiane Gomes de Macedo Bacurau; Diego Salvador Muniz da Silva; Deborah Carvalho Malta; Flávia Silva Arbex Borim
ABSTRACT Objective: To estimate the prevalence of multimorbidity in long-lived Brazilian individuals (age ≥80 years) and to associated it with the use of health services. Methods: Cross-sectional population-based study with data from the 2019 National Survey of Health (n=6,098). Frequencies of use of services were estimated for older people with multimorbidity and according to sex, health insurance ownership, and self-rated health. The prevalence rates, crude and adjusted prevalence ratios, and the respective 95% confidence intervals were calculated. Results: The average age of the older adults was 85 years and about 62% were women; the prevalence of multimorbidity was 57.1%, higher in women, in those who have health insurance, and who reside in the southern region of the country (p<0.05). In the oldest old with multimorbidity, the use of services in the last 15 days reached 64.6%, and more than 70% were hospitalized in the last year or did not carry out activities in the previous two weeks for health reasons. Differences were observed for the indicators of service use in relation to sex, health insurance ownership, and self-rated health, according to multimorbidity. Conclusion: Indicators for the use of health services were higher in older individuals who have two or more chronic diseases, regardless of sociodemographic conditions and self-rated health, showing the impact of multimorbidity per se in determining the use of services among the oldest old.